Sea Level Change: Mapping Danish Municipality Needs for Climate Information - Madsen, Kristine S.; Murawski, Jens; Blokhina, Marina; Su, Jian (Frontiers in Earth Science, 2019)
Climate change will affect the coastline of the Baltic Sea through changes in sea level, storm surges and waves. In Denmark, a large part of the responsibility for climate adaptation lies with the local municipalities. The purpose of this study was to map the user needs for coastal climate change information of five municipalities in the Danish south western Baltic Sea and the Danish Coastal Authority in a cost-efficient way and to transform the mapping into local climate indicators. An interview template was customized to form the basis for telephone interviews of key stakeholders and systematic gathering of the results. The interest for the interviews was high, and response from the interviewed persons on the use of the template was very positive. During the interviews, it was clear that the municipalities have access to extensive information on the population and infrastructure, as well as detailed geographical information. The main interests were in very high quality storm surge warnings and present day and future extreme sea level and wave heights. This should be based on modeling of past storm surges and future changes, taking observations, and historical records into account. There was a big need for more detailed information than presently available, and for common scenarios, which will help the collaboration between municipalities. Within this study, the user requirements were used to define targeted climate indicators. Within the C3S CODEC project, the indicators will be provided for the municipalities, based on a downscaling of European scale storm surge, and wave simulations to local scale.